Hubungan tingkat stres dengan kejadian dismenore pada remaja putri - Lintang Teja Putri; Diah Nur Annisa; Sri Riyana (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Dysmenorrhea in adolescent girls not only causes physical pain but also impacts academic performance and quality of life. This condition can lead to decreased concentration, limited activity, and school absence. Repeated monthly impacts have the potential to trigger stress, which can further exacerbate menstrual pain through disruption of the neuroendocrine system, increasing uterine contractions and pain perception. Purpose: To determine the relationship between stress levels and the incidence of dysmenorrhea in adolescent girls. Method: This quantitative study used a cross-sectional design. The sample consisted of 61 adolescent girls who had experienced menstruation and were selected using a purposive sampling technique. Data were collected using the Depression Anxiety Stress Scales 42 (DASS-42) questionnaire and a questionnaire about dysmenorrhea. Data were analyzed univariately and bivariately using correlation tests. Results: The p-value = 0.000 with r = 0.762, indicating a significant relationship between stress levels and the incidence of dysmenorrhea. The higher the stress level, the more severe the dysmenorrhea. Conclusion: There is a significant relationship between stress levels and the incidence of dysmenorrhea in adolescent girls. Therefore, stress management needs to be a priority in promotive and preventive efforts to prevent and mitigate the impact of dysmenorrhea in adolescents.   Keywords: Adolescent Girls; Dysmenorrhea; Menstruation; Stress Level.   Pendahuluan: Dismenore pada remaja putri tidak hanya menimbulkan nyeri fisik, tetapi juga berdampak pada aktivitas belajar dan kualitas hidup. Kondisi ini dapat menyebabkan penurunan konsentrasi, keterbatasan aktivitas, serta ketidakhadiran di sekolah. Dampak yang berulang setiap bulan berpotensi memicu stres yang selanjutnya dapat memperberat nyeri haid melalui gangguan sistem neuroendokrin sehingga meningkatkan kontraksi uterus dan persepsi nyeri. Tujuan: Untuk mengetahui hubungan tingkat stres dengan kejadian dismenore pada remaja putri. Metode: Penelitian kuantitatif dengan desain cross-sectional. Sampel berjumlah 61 remaja putri yang telah mengalami menstruasi dan dipilih menggunakan teknik purposive sampling. Data dikumpulkan menggunakan kuesioner Depression Anxiety Stress Scales 42 (DASS-42) dan kuesioner kejadian dismenore. Analisis data dilakukan secara univariat dan bivariat menggunakan uji korelasi. Hasil: Nilai p-value = 0.000 dengan r = 0.762 yang menandakan adanya hubungan signifikan antara tingkat stres dengan kejadian dismenore artinya semakin tinggi tingkat stres maka semakin berat dismenore yang dirasakan. Simpulan: Terdapat hubungan yang signifikan antara tingkat stres dengan kejadian dismenore pada remaja putri. Sehingga pengelolaan stres perlu menjadi perhatian dalam upaya promotif dan preventif untuk mencegah serta mengurangi dampak dismenore pada remaja.   Kata Kunci: Dismenore; Menstruasi; Remaja Putri; Tingkat Stres.